2018
DOI: 10.3390/nu10050543
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Molecular Mechanism Underlying the Inhibitory Efficacy of Taiwanese Local Pomegranate Peels against Urinary Bladder Urothelial Carcinoma

Abstract: Pomegranate (Punica granatum L.) fruit has been demonstrated to have the inhibitory activities to various tumors. In this study, we try to uncover the molecular mechanism underlying the inhibitory capability of Taiwanese local pomegranate fruit to urinary bladder urothelial carcinoma. The results collected from the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay indicated that the ethanol extract of pomegranate peel exhibited better inhibitory activity to human urinary bladder urothelial car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Few studies have been done regarding the protective effect of pomegranate against BC. All of them were In vitro studies ( Chang et al., 2018 ; Lee et al., 2013 ; Zhou et al., 2015 ). Therefore, we decided in the present study to investigate the effectiveness of PJ in inhibiting BC induced by N -butyl- N -(4-hydroxybutyl)-nitrosamine (BBN) in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been done regarding the protective effect of pomegranate against BC. All of them were In vitro studies ( Chang et al., 2018 ; Lee et al., 2013 ; Zhou et al., 2015 ). Therefore, we decided in the present study to investigate the effectiveness of PJ in inhibiting BC induced by N -butyl- N -(4-hydroxybutyl)-nitrosamine (BBN) in rats.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the anticancer effects and mechanisms of pomegranate action is presented in Figure 1. cell proliferation [41], glycolysis [53][54][55], and cell cycle [59,60] as well as apoptosis [23,41,42,47,48,51,53,54,61,62,69,71]. The summary of anticancer effects and mechanisms of pomegranate action.…”
Section: Pomegranate In Bladder Cancer Preventionmentioning
confidence: 99%
“…Pomegranate ( Punica granatum L.) is an edible fruit widely grown in Mediterranean countries, northern India, northern/southern America, Europe, and even in Taiwan, mainly as gardening trees [ 23 ]. Pomegranate fruits consist of white to dark purple edible seeds embedded in a white spongy astringent membrane surrounded by a thick reddish skin or pericarp.…”
Section: Pomegranatementioning
confidence: 99%
“…Several in vitro and in vivo studies demonstrated the anticancer effect of PP and its constituents (Adhami et al, 2009) different cancer types, that is, colon (Waly et al, 2014), liver (Li et al, 2019), thyroid Liu et al, 2017), uterine, breast (Dikmen et al, 2011;Fazio et al, 2018), bladder (Chang et al, 2018), prostate (Deng et al, 2017), leukemia (Panth et al, 2017), and osteosarcoma (Li et al, 2014). Moreover, its ellagitannins enhanced the chemotoxicity of 5-fluorouracil in colorectal cancer cell lines through apoptosis potentiation and to lessen its side effects in rats (Chen, Lam, et al, 2018).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Anti-tumor action mechanisms of PPE and its constituents is exerted via multiple targets, that is, antioxidant (Waly et al, 2014), antiangiogenic (Ceci et al, 2018;Naseri et al, 2018), anti-proliferative (Dikmen et al, 2011;Fazio et al, 2018;Li, Ye, et al, 2017;Li, Liu, et al, 2017), anti-metastatic (Deng et al, 2017;, and apoptosis induction (Chang et al, 2018;Li et al, 2019). Furthermore, it inhibited several oncogenic signaling pathways, for example, NF-κB, PI3K/AKT/Mtor (Khwairakpam et al, 2018), oncogenes expression responsible for cancer development (e.g., anti-apoptotic genes (Dikmen et al, 2011), and MMPs (Deng et al, 2017;Khwairakpam et al, 2018;Li, Ye, et al, 2017;Li, Liu, et al, 2017), concurrent with the induction of pro-apoptotic protein caspase-3 activity Deng et al, 2017;Li et al, 2014), BCL-2-associated X protein/B-cell lymphoma 2 (Bax/Bcl-2) ratio (Deng et al, 2017;Dikmen et al, 2011;Li et al, 2014) and the apoptosis-associated protein, P53, expression (Song et al, 2016).…”
Section: Anticancer Activitymentioning
confidence: 99%